Interventions of Brazil's more doctors program through continuing education for Primary Health Care - Pereira, Laianny Krizia Maia; Silva, José Adailton da; Valentim, Ricardo A. de M.; Lima, Thaísa G. F. M. S.; Gusmão, Cristine M. G.; Rocha, Marcela A. da; Santos, Marquiony M. dos; Caitano, Alexandre R.; Barros, Rosires M. B. de; Rosendo, Tatyana Souza (Frontiers in Public Health, 2024)
Introduction Brazil's More Doctors Program, in its training axis, aims to improve medical training for Primary Health Care through interventions related to the reality of the territory. The research presented here analyzed the interventions implemented by Brazil's More Doctors Program physicians, members of the Family Health Continuing Education Program, and the relationship with Primary Health Care programmatic actions. Methodology The research conducted made use of Text and Data Mining and content analysis. In total, 2,159 reports of interventions from 942 final papers were analyzed. The analysis process was composed of the formation of the corpus; exploration of the materials through text mining; and analysis of the results by inference and interpretation. Results It was observed that 57% of the physicians worked in the Northeast Region, which was also the region with the most interventions (66.8%). From the analysis of the bigrams, trigrams, and quadrigrams, four constructs were formed: “women's health,” “child health,” “chronic non-communicable diseases,” and “mental health.” Terms related to improving access, quality of care, teamwork, and reception were also present among the N-grams. Discussion The interventions carried out are under the programmatic actions recommended by the Brazilian Ministry of Health for Primary Health Care, also addressing cross-cutting aspects such as Reception, Teamwork, Access Improvement, and Quality of Care, which suggests that the training experience in the Family Health Continuing Education Program reflects on the way these professionals act.